1991
DOI: 10.1093/geront/31.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Unfit Survivors: Exercise as a Resource for Aging Women

Abstract: Some researchers have suggested that about 50% of aging decline is preventable through improved life-style habits such as participation in regular exercise, yet exercise as a resource for healthier survival is being ignored by many aging women. Though recent research findings highlight regular physical activity as a potent factor in combatting hypokinesis (the disease of inactivity), numerous real and perceived barriers to exercise stand between the older woman and her ability to achieve a better quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 0 publications
0
28
1
Order By: Relevance
“…To lim it one's activity to only that needed for aero bic fitness may compromise other needs of the body for overall muscle strength and en durance, joint flexibility, balance and upright posture [16], However, the elderly have been shown to adapt more slowly to physical stress [17], thus they may actually need programs designed with more specific goals for the indi vidual. For example, an individual that needs to improve strength would benefit from a pro gram that specifically focuses on muscle exer cises, whereas another participant that needs to lose weight and improve cardiovascular fit ness may benefit from a program that concen trates on low intensity aerobic activity of lon ger duration.…”
Section: Discussionmentioning
confidence: 99%
“…To lim it one's activity to only that needed for aero bic fitness may compromise other needs of the body for overall muscle strength and en durance, joint flexibility, balance and upright posture [16], However, the elderly have been shown to adapt more slowly to physical stress [17], thus they may actually need programs designed with more specific goals for the indi vidual. For example, an individual that needs to improve strength would benefit from a pro gram that specifically focuses on muscle exer cises, whereas another participant that needs to lose weight and improve cardiovascular fit ness may benefit from a program that concen trates on low intensity aerobic activity of lon ger duration.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the ageing process and sedentary life style, elders classically experience a decline in physical functioning and an increase in the incidence of chronic health problems. Research studies have indicated that exercise is a recommended behaviour to prevent, delay and manage many chronic illnesses in elders (O'Brien & Vertinsky 1991, Lowenthal et al 1994, Clark 1996. Selecting an appropriate activity to keep the older population active and, most importantly, incorporating this activity as a part of their daily life, is essential to enhance their well-being and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Since women significantly outnumber and also outlive men by an average of 7 or 8 years, they will make up the majority of this population [1]. The advanced years of life are often filled with chronic illness, reducing the quality of life and decreasing the individual's ability to perform activities of daily living [1,2].…”
Section: Introductionmentioning
confidence: 99%